(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: Ulcerative colitis is a chronic refractory inflammatory disease affecting the colon. Several drugs have been developed for it, nevertheless, there are limitations in the therapy due to the inadequate responses and significant undesirable effects. Therefore, novel safer drugs with more therapeutic efficacy are needed. Objective: To investigate the potential anti-inflammatory effects and histological outcome of artemisinin in acetic acid-induced ulcerative colitis in rats. Methods: Rats with colitis were received either artemisinin 100 mg/kg or sulfasalazine 100 mg/kg orally for 7 days. Macroscopical and microscopical assessment, the measurement of the colonic cytokines (tumor necrosis factor-alpha (TNF-?) and interleukin-4 (IL-4)), myeloperoxidase (MPO), and E-Selectin. Results: Both macroscopical lesion area and histological colonic damage induced by acetic acid were significantly reduced by artemisinin and sulfasalazine accompanied by attenuation of the elevated colonic TNF-?, IL-4, MPO activity and E-Selectin. Conclusion: Artemisinin had an effective role in experimental colitis in rats through anti-inflammatory and antioxidant actions. Keywords: Acetic acid, artemisinin, oxidative stress, E-Selectin, ulcerative colitis, IL-4 Citation: Abdullah HR, Abd AH, Qasim BJ. Artemisinin attenuates inflammation in rats with ulcerative colitis through inhibition of inflammatory biomarkers, oxidative stress and adhesion molecules. Iraqi JMS. 2020; 18(2): 155-163. doi: 10.22578/IJMS.18.2.10